THE TECHNOLOGY INDUCTION FOR PREVENTING LIVESTOCK OF ANIMAL FEED FARMER GROUPS IN DISTRICT OF EAST LAMPUNG - Sulistiyanti, Sri Ratna; Hartono, Madi; Wijaya, Agung Kusuma (Universitas Negeri Medan, 2017)
AbstractThe common problem of livestock is abundant greenery during the rainy season and shortages in the dry season. The condition is bad for the health and productivity of livestock Preservation of animal feed technology is conducted by a team from Institute of Research and Community Service (LPPM) of Universitas Lampung, in Toto Mulyo Village, Way Bungur District, East Lampung. The purpose of the processing and preservation of forage feed source of fiber is to utilize forage in the rainy season, maintain the quality of forage, overcome the difficulty of forage in the dry season, improve the quality of forage fiber sources that have low nutrient content. Preservation technique is made silage (to maintain the quality of forage), while to improve the forage quality is done by fermentation and amoniation. The activities were carried out with the design of preserved livestock feeding equipment, training on the use and care of targeted farmer groups (Karya Makmur and Jati Diri 6), group management assistance, the handover of the preserved animal feed technology package, and formed a pilot group. The result of community service is a package of livestock feed preservation technology (silage and ammoniasi).Keywords: ammoniation, livestock feed preservation, fermentation, productivity, silage